Unpacking Rigor and Methodological Consistency in Sustainability-Related Case Study Research - Fidan, Selahaddin samil (WILEY, 2026)
In organizational research, the extent to which case study articles adhere to rigor criteria is analyzed; however, a similar assessment in the sustainability field is lacking. This study aims to systematically examine the extent to which case study articles published in two leading journals in the sustainability field satisfy quality criteria and demonstrate methodological coherence. The research findings reveal that there are several problematic practices related to the implementation of quality criteria in the sustainability field. Although sustainability researchers largely provide satisfactory explanations for their rationale in choosing the case study methodology and their case selection processes, there remain concerning methodological inconsistencies between their case study approaches and data analysis. Additionally, the research findings have identified deficiencies in the application of fundamental transparency criteria regarding the background and procedural details of interview data in sustainability articles, such as the failure to report interview duration, the omission of the interview language, and the lack of presentation of the interview questions. Furthermore, although case study articles report the use of document and observation data, this study finds that evidence related to these types of data is not sufficiently presented in the research findings section. The research findings regarding the quality criteria for data analysis reveal that researchers are subject to the ceremonial data analysis problem (e.g., merely referencing a specific data analysis technique without providing methodological interpretation or reflexive explanation) when reporting their data analysis. Although they make superficial references to conducting a more rigorous qualitative research design and reference the concept of triangulation, the findings demonstrate a lack of concrete evidence and methodological reflection demonstrating how these criteria are actually met. This study highlights both problematic practices and exemplary applications regarding quality criteria and also offers methodological recommendations for improving problematic practices. Finally, the implications of the research findings for scholars, reviewers, and editors are also discussed.
Keywords: case study research; methodological consistency; rigor; sustainability; QUALITATIVE RESEARCH; INTERNATIONAL-BUSINESS; DATA SATURATION; CASE SELECTION; SCIENCE; MANAGEMENT; INTERVIEWS; CRITERIA; FIELD; Business & Economics; Environmental Sciences & Ecology